Migration, Diversity, and Economic Growth. (January 2017) - Bove, Vincenzo; Elia, Leandro
Highlights: Data on global bilateral migration during 1960–2010 to compute diversity indices. Gravity-based instrumental variable strategy to overcome endogeneity issues. Fractionalization and polarization have positive impacts on economic growth. Developing economies seem to benefit the most from diversity. Summary: When migrants move from one country to another, they carry a new range of skills and perspectives, which nurture technological innovation and stimulate economic growth. At the same time, increased heterogeneity may undermine social cohesion, create coordination, and communication barriers, and adversely affect economic development. In this article we investigate the extent to which cultural diversity affects economic growth and whether this relation depends on the level of development of a country. We use novel data on bilateral migration stocks, that is the number of people living and working outside the countries of their birth over the period 1960–2010, and compute indices of fractionalization and polarization. In so doing, we explore the effect of immigration on development through its effect on the composition of the destination country. We find that overall both indices have a distinct positive impact on real GDP per capita and that the effect of diversity seems to be more consistent in developing countries.